Fluorescence evaluations for porphyrin formation during topical PDT using ALA and methyl-ALA mixtures in pig skin models - Fujita, Alessandra Keiko Lima; Rodrigues, Phamilla Gracielli Sousa; Requena, Michelle Barreto; Escobar, André [UNESP]; da Rocha, Rozana Wendler [UNESP]; Nardi, Andrigo Barboza de [UNESP]; Kurachi, Cristina; de Menezes, Priscila Fernanda Campos; Bagnato, Vanderlei S. (Elsevier, 2016)
Background Photodynamic Therapy (PDT) using Aminolevulinic acid (ALA) and derivative molecules as topical medication and as a precursor of protoporphyrin (PPIX), is limited due to low permeation through skin or efficiency in porphyrin production. This behavior affects the production and homogeneity of PPIX distribution on superficial skin and in the deeper skin layers. Many authors propose alternatives to solve this such as, modification in the ALA and derivativemolecules, modifying the chemical properties of emulsion external phase or incorporating a delivery system to the emulsion. The goal of this study is to discuss what proportion of ALA and Methyl aminolevulinate (MAL) on mixtures increase the amount and uniformity of PPIX formation at superficial skin by fluorescence evaluations. Methods The study was conducted in vivo using a pig skin model. PPIX production was monitored using fluorescence spectroscopy and widefield fluorescence imaging on skin surface. 20% of ALA and MAL cream were done mixing the following proportions: ALA, M2 (80% ALA–20% MAL), M3 (60% ALA–40% MAL), M4 (50% ALA–MAL), M5 (40% ALA–60% MAL), M6 (20% ALA–80% MAL) and MAL. Results Mixtures M3, M4, and M5 showed the most PPIX production on skin by widefield fluorescence imaging and fluorescence spectroscopy in 3 h of incubation. These results suggest that 50% of ALA and MAL in the same mixture increase the PPIX production in amount, homogeneity and time production when compared to ALA and MAL. This has a positive impact on photodynamic damage optimizing the PDT treatment.
Keywords: 5-ALA; 5-MAL; Fluorescence spectroscopy; Photodynamic therapy; Porphyrin; Widefield fluorescence imaging